2006
DOI: 10.1681/asn.2005111197
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Electrolyte–Driven Responses in the Renal WNK Kinase Pathway In Vivo

Abstract: T he role of WNK1 and WNK4 in control of electrolyte balance and BP first became apparent with their mutation being associated with familial hyperkalemic hypertension (FHHt; also known as Gordon syndrome and pseudohypoaldosteronism type 2), a human autosomal dominant disorder that features hypertension, hyperkalemia, and acidosis that usually are hyperresponsive to thiazide diuretics (1,2). FHHt can be caused by intronic deletions in WNK1 or missense mutations in WNK4 (3). Mutations in either cause a broadly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
114
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 39 publications
9
114
1
Order By: Relevance
“…mRNA expression of L-WNK1 and KS-WNK1 and protein ex- pression of L-WNK1 were measured in the kidney of 16-week-old C57BL/6N mice fed with a normal, low-sodium, or high sodium diet, submitted to a potassium load or a chronic aldosterone infusion for 10 days (Supplemental Table S2). In agreement with a previous study, 21 we confirmed that aldosterone and potassium load led respectively to a 1.6-and 1.5-fold increase in KS-WNK1 mRNA expression (Supplemental Figure S3) and that L-WNK1 mRNA expression is unaffected by the different challenges ( Figure 5A). At the protein level, L-WNK1 was not modified by changes in Na ϩ or K ϩ intake but was significantly increased by aldosterone infusion (1.9 Ϯ 0.17 versus 1 Ϯ 0.12 in control animals; Figure 5B).…”
Section: Mir-192 Expression Is Regulated By Nasupporting
confidence: 93%
See 2 more Smart Citations
“…mRNA expression of L-WNK1 and KS-WNK1 and protein ex- pression of L-WNK1 were measured in the kidney of 16-week-old C57BL/6N mice fed with a normal, low-sodium, or high sodium diet, submitted to a potassium load or a chronic aldosterone infusion for 10 days (Supplemental Table S2). In agreement with a previous study, 21 we confirmed that aldosterone and potassium load led respectively to a 1.6-and 1.5-fold increase in KS-WNK1 mRNA expression (Supplemental Figure S3) and that L-WNK1 mRNA expression is unaffected by the different challenges ( Figure 5A). At the protein level, L-WNK1 was not modified by changes in Na ϩ or K ϩ intake but was significantly increased by aldosterone infusion (1.9 Ϯ 0.17 versus 1 Ϯ 0.12 in control animals; Figure 5B).…”
Section: Mir-192 Expression Is Regulated By Nasupporting
confidence: 93%
“…؉ or K ؉ Intake and Aldosterone KS-WNK1 mRNA expression is stimulated by aldosterone, 21,22 whereas L-WNK1 expression is unaffected. We asked if L-WNK1 expression could be regulated at the post-transcriptional level.…”
Section: Mir-192 Expression Is Regulated By Namentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that both WNK4 and KLHL3 are present in the thick ascending limb of Henle (TAL), distal convoluted tubule (DCT), connecting tubule (CNT), and collecting duct (CD) (2,4,26,38). Levels of KLHL3 S433-P in nephrons of mice on a high-salt diet with and without AII infusion (five mice in each group) was compared by immunofluorescence microscopy.…”
Section: Aii Signaling Prevents Klhl3-mediated Reduction Of Wnk4 In Hekmentioning
confidence: 99%
“…12 Furthermore, it has been proposed that the molecular switch for the splicing of L-WNK1 and KS-WNK1 is affected by the amount of dietary potassium intake. [19][20][21] In this study, we investigated whether the common variations in the WNK1 gene are potential contributors to individual variations in blood pressure. Furthermore, we analyzed the interactions between the common WNK1 variants and dietary potassium and sodium intake for determining inter-individual variations in blood pressure.…”
Section: Introductionmentioning
confidence: 99%